A Review of Marketing Channel Implications in Agribusiness - Hanafie, Saliha G; Bandera, Abdani D. (Indonesian Journal Publisher, 2025)
This review analyzes the impacts of transformations in agribusiness marketing channels, specifically supermarket expansion, value-chain governance, and digitalization on value distribution, smallholder inclusion, and overall system competitiveness. Using an integrative qualitative review, the study synthesizes evidence from recent academic literature, institutional reports, and policy analyses published over the last two decades. Findings show that modern retail growth enhances quality control and procurement efficiency but often excludes smallholders unable to meet stringent standards and capital requirements. Governance dynamics further shape distributional outcomes, as concentrated buyer power allows lead firms to influence pricing, compliance costs, and coordination structures, reinforcing asymmetries unless counterbalanced by supportive policies, transparent contracting, and stronger farmer organizations. Digitalization offers new pathways for efficiency and market access through e-commerce platforms, traceability systems, and data-driven coordination, yet its benefits remain uneven due to digital divides, limited infrastructure, and unclear data governance frameworks. The results highlight that modernization alone does not guarantee inclusivity. Building resilient and equitable agrifood systems requires integrated strategies that combine technological innovation with fair governance arrangements, institutional support, and targeted policies that enable smallholders to upgrade and participate in evolving market channels.